THE DRUG CASED PRISONERS’ INTELLECTUAL WELL-BEING AND HABIT BASED ON BUDDHIST PRINCIPLES - Linphoo, Montree; Phrayai, Narumol; Prasertsin, Ujsara; Jinngee, Prateep (Journal of Buddhist Anthropology, 2020)
This research being qualitative is aimed to study the drug cased prisoners’ intellectual well-being and habit based on Buddhist principles. The key informants were 12 people including three Buddhist experts, three Buddhist chaplains, three social workers and three drug cased prisoners selected by purposive sampling. The experts were selected depending on the personal profile and the specific aptitude, while the drug cased prisoners were selected by investigating the personal profile, the offense case and the authorities’ guide. The tools for data collection were semi-structured in-depth interview forms relating to the drug cased prisoners’ intellectual well-being and habit based on Buddhist principles which yielded the reliabilities of 0.60-1.00. The data collection was by way of in-depth interview basically determined the interview questions with the document analysis and related research. Research data were analysed with content analysis. The result of this research was found that 1) The drug cased prisoners’ intellectual well-being based on Buddhist principles consists of knowing, awakening and delighting which is the ability to diagnose the conscience, to develop the mindfulness, compassion and to do supportively the duties relying on importantly their habit in living. 2) The drug cased prisoners’ habit based on Buddhist principles was categorized as sensual pleasure habit meaning to spent their life for seeking the happiness based on senses(eyes, ears, nose, tongue and body)in order to response their satisfaction.